2020
DOI: 10.3389/fpsyg.2019.02859
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Care: A National Survey on the Prevalence, Demographic Characteristics and Health Problems Among Young Adult Carers Attending Higher Education in Norway

Abstract: The aim of the present study was to examine prevalence, characteristics and health outcomes among young adults (18 to 25 years) who provide informal care to family members or others with physical or mental illnesses, substance misuse or disabilities. Design: The sample was obtained from a national survey in Norway from 2018 among students in higher education (the SHoT2018-study). The current sample comprise 40,205 participants, 70.2% women, mean age 22 years (SD = 1.7). Outcome Measures: Participants answered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
77
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(94 citation statements)
references
References 28 publications
9
77
2
6
Order By: Relevance
“…Their caring tasks can be time-consuming. A recent study found that adolescents and young adults with caring roles spent about 3–5 h helping each day (Haugland et al 2019 ). Due to their responsibilities, these young carers’ day-to-day lives can be stressful (e.g., Ali et al 2012 ), with potential risks to their own mental health (e.g., Dharampal and Ani 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their caring tasks can be time-consuming. A recent study found that adolescents and young adults with caring roles spent about 3–5 h helping each day (Haugland et al 2019 ). Due to their responsibilities, these young carers’ day-to-day lives can be stressful (e.g., Ali et al 2012 ), with potential risks to their own mental health (e.g., Dharampal and Ani 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have included indicators for the socioeconomic background as covariates when comparing mental health outcomes between young carers and their peers. These studies showed that poorer outcomes among young carers could not be explained by family context variables only (e.g., Haugland et al, 2019;Tseliou et al, 2018). However, viewed from an ecological perspective, development in different areas, including mental health, results from the interactions between the person and the environment (e.g., Tomasetti, 2016).…”
mentioning
confidence: 99%
“…Caring has especially been linked to stress, anxiety and depression symptoms when occurring in the adolescent phase [ 10 , 11 ], which is remarkable given evidence that most mental health problems that start during adolescence subsequently persist into adulthood [ 12 ]. Risk factors that have been reported to affect physical and mental health outcomes of adolescent YCs (AYCs) include being female or non-binary and having a migration background [ 8 , 13 ], living with care recipients [ 8 ], the extent (i.e., greater amount of time) [ 13 , 14 , 15 ] and nature (i.e., personal and emotional care, financial and practical management) [ 7 , 14 ] of caring activities and food insecurity [ 16 , 17 ]. AYCs are also likely to face difficulties in education that negatively impact future employability, career aspirations and socioeconomic status [ 5 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, no resilience-based intervention for AYCs has yet been tested in Europe. In Australia, a resilience-based program for children (aged [12][13][14][15][16][17][18] of parents with a mental illness was evaluated [41]. However, allocation of the 44 participating AYCs to intervention or control groups was not randomized.…”
Section: Introductionmentioning
confidence: 99%